2020
DOI: 10.1590/0103-8478cr20190491
|View full text |Cite
|
Sign up to set email alerts
|

Different tray cell volumes for lettuce grown in conventional and hydroponic system

Abstract: Nowadays, an important economic movement is involved in the improvement of polyethylene trays for the production of seedlings, being developed with different volumes, numbers and cell formats in an each culture-specific manner. The objective of the present study was to evaluate the performance of curly lettuce originated from seedlings from trays with different volumes, through the comparison between conventional and hydroponic-NFT cultivation. Five volumes of trays (10, 20, 30, 40 and 50 cm³ of cell-1) were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…The plant height showed significant positive correlation at 5% probability, with the shoot dry mass, 0.58 g (Figure 2). These results are in accordance with Ceccherini et al (2020) who, evaluating the crispleaf Vanda under hydroponic system, found plants ranging from 19 to 28 cm plant -1 .…”
Section: Genotypessupporting
confidence: 92%
See 1 more Smart Citation
“…The plant height showed significant positive correlation at 5% probability, with the shoot dry mass, 0.58 g (Figure 2). These results are in accordance with Ceccherini et al (2020) who, evaluating the crispleaf Vanda under hydroponic system, found plants ranging from 19 to 28 cm plant -1 .…”
Section: Genotypessupporting
confidence: 92%
“…The number of lettuce leaves is one important trait, since the leaves are the product to be consumed when it comes to this vegetable, so that one genotype which shows a greater number of leaves stands out among the others. Ceccherini et al (2020), evaluating crispleaf lettuce Vanda under hydroponic system, found 27 leaves per plant, approximately. The light interception, which will be converted into chemical energy, is facilitated when a greater number of leaves can be noticed; so, plants with more leaves will show a faster development, will be more vigorous and can be even early (Taiz et al, 2017).…”
Section: Genotypesmentioning
confidence: 99%
“…They obtained 183.4 g and 124.5 g of fresh biomass per plant for the cultivar Verônica, respectively. On the other hand, Ceccherini et al (2020) studied a different number of tray cells for lettuce production under conventional and hydroponic systems for summer cultivation. They obtained a fresh mass of about 280 g plant −1 .…”
Section: Fertilizermentioning
confidence: 99%
“…Certain aspects of seedling production management (CLÁUDIO et al, 2020;VETRANO et al, 2020) determine seedling quality and consequently their production. In a work assessing the effect of seedling production tray cell volumes on the quality of seedlings, CECCHERINI et al (2020) found that factors related to the cell volume affect their quality and production performance. These results highlight the importance of high quality seedlings and exemplify the need for studies determining transplant quality.…”
Section: Introductionmentioning
confidence: 99%